Longitudinal assessment of changes in psychosocial functioning of patients with adolescent idiopathic scoliosis using virtual reality before, during and after treatment: a quantitative and qualitative study - Misterska, Ewa; Głowacki, Maciej (Journal of Medical Science, 2020)
This project aims to longitudinally assess changes in the psychosocial functioning of females with adolescent idiopathic scoliosis before and after completion of surgical treatment and implementation of cognitive-behavioural therapy. The planned study is a longitudinal randomised trial with 1-year follow-up. The cross-sectional aspect of the research concerns differences in perception of body shape from the perspective of the patients, their doctors, and healthy female adolescents. This study will recruit 106 patients treated at the Department of Pediatric Orthopaedics and Traumatology, Poznan University of Medical Sciences, their doctors and 106 healthy female controls. It will be the first study to use biometric self-avatars in virtual reality to investigate changes within body representation in scoliosis. The study findings will inform the development of guidelines for interdisciplinary rehabilitation of scoliosis patients following surgical treatment.